Parent Satisfaction With Care and Treatment Relates to Missed Nursing Care in Neonatal Intensive Care Units - Lake, Eileen T.; Smith, Jessica G.; Staiger, Douglas O.; Hatfield, Linda A.; Cramer, Emily; Kalisch, Beatrice J.; Rogowski, Jeannette A. (Frontiers in Pediatrics, 2020)
Background: The satisfaction of parents of infants in neonatal intensive care is important to parent-infant bonding and the parents’ ability to care for the baby, including after discharge. Given the principal caregiving role of nurses in this setting, parent satisfaction is influenced by high quality nursing care. Required nursing care that is missed, such as counseling and support, might influence parent satisfaction. How missed nursing care relates to parent satisfaction is unknown. Objective: To describe the satisfaction of parents of infants in neonatal intensive care and determine how satisfaction relates to missed nursing care in a sample of U.S. nursing units. Methods: The design was cross-sectional and correlational. Thirty neonatal intensive care units that participate in the National Database of Nursing Quality Indicators were recruited. To maximize sample variation in missed care, the highest and lowest quartile hospitals on missed nursing care, measured by nurse survey, were eligible. Ten parents of infants who were to be discharged were recruited from each site to complete a survey. Parent satisfaction was measured by the EMPATHIC-38 instrument, comprising five subscales: information, care and treatment, organization, parental participation, and professional attitude, and a total satisfaction score. Multivariate regression models were estimated. Results: Parent satisfaction was high (5.70 out of 6.00). The prevalence of missed care was 25% and 51% for low and high missed care units, respectively, and 40% for all units. On average, nurses missed 1.06 care activities; in the low and high missed care units the averages were 0.46 and 1.32. Over ten percent of nurses missed activities that involved the parent, e.g., teaching, helping breastfeeding mothers, and preparing families for discharge. A one standard deviation decrease in missed care activities at the unit level was associated with a 0.08-point increase in parent satisfaction with care and treatment (p=0.01). Conclusion: Parents in U.S. neonatal intensive care units are highly satisfied. Neonatal intensive care nurses routinely miss care. Parent satisfaction with care and treatment is related to missed nursing care. Nursing care missed relates primarily to the care of the baby by the parents, which could have long term health and developmental consequences.